State selective fragmentation of doubly ionized sulphur dioxide - M. Jarraya; M. Wallner; G. Nyman; S. Ben Yaghlane; M. Hochlaf; J. H. D. Eland; R. Feifel (Scientific Reports, 2021)
Abstract Using multi-electron–ion coincidence measurements combined with high level calculations, we show that double ionisation of SO2 at 40.81 eV can be state selective. It leads to high energy products, in good yield, via a newly identified mechanism, which is likely to apply widely to multiple ionisation by almost all impact processes.